“Elaboración de un Proyecto de Factibilidad para la Implementación de un Frigorífico para la Comercialización de Productos Cárnicos Y Embutidos, en la Ciudad de Zumba, perteneciente al Cantón Chinchipe Provincia de Zamora Chinchipe - Jaramillo Yaguana, Mercedes Karina (2017)
The present research work was carried out in the city of Zumba, aiming to present a proposal for the implementation of a commercialization of meat and sausage products. This project is aimed at meeting the demand for this type of products, in order to meet viable goals, the following objectives were proposed: Carry out a market study to determine the conditions of supply and demand; Conduct the technical study to determine the technology requirements; The financial study to establish the amount of investment required, the cost of marketing and sales prices; Perform the financial assessment to determine the profitability of the proposed project. In order to fulfill the objectives, the following research methods and techniques were used: The deductive method, for the theoretical foundation; The inductive method, to determine tastes and preferences through the application of the survey; The descriptive-analytical method, to know the current situation of the meat, its processing and market requirements, among the techniques we have: Observation, allowed to observe the processes of marketing of sausages; The survey was applied to a population sample of 270 families in the city of Zumba and 14 bidders to determine the demand and supply conditions of sausages and meat products. This work focuses on aspects such as: Market Study, which with the support of methods, techniques and procedures allowed to determine the current and future demand and also to know the behavior of the competition. 5 It establishes the size and location of the company for a marketing of 45.864 pounds of meat and sausage a year, it also describes the marketing process, the machinery to be used and the staff that will be part of the company "MARKETING LA ZUMBEÑITA". The following is a financial study detailing the investments and financing required to start the project; In addition, the financial evaluation, which constitutes one of the fundamental parts that allows establishing the feasibility of the same, analyzes the main indicators as the Net Present Value of $ 23,940 dollars; Internal Rate of Return of 38.78%; Benefit Ratio Cost of $ 1.08 per dollar invested the company earns 0.08 cents; Period of Capital Recovery is 2 years, 8 months and 23 days; Sensitivity Analysis indicates that the project supports an increase in costs of 4.28% and the analysis of sensitivity in the decrease of revenues of 3.88%; Which determine a feasible situation for the execution of the project, finally includes the conclusions and recommendations, product of the present investigation, which will allow to operate in a better way to the project.